Dietary intakes and plasma concentrations of carotenoids and tocopherols in relation to glucose metabolism in subjects at high risk of type 2 diabetes: the Botnia Dietary Study - Ylönen, Katriina; Alfthan, Georg; Groop, Leif; Saloranta, Carola; Aro, Antti; Virtanen, Suvi M (The American journal of clinical nutrition, 2003)
The role of antioxidants in the pathogenesis of type 2 diabetes is uncertain. We evaluated cross-sectional relations of dietary intakes and plasma concentrations of antioxidants with glucose metabolism in a high-risk population. The subjects were 81 male and 101 female first- and second-degree, nondiabetic relatives of patients with type 2 diabetes. Antioxidant intake data were based on 3-d food records. Subjects taking supplements containing beta-carotene or alpha-tocopherol were excluded. Plasma antioxidant concentrations were measured by HPLC. By using multiple linear regression analysis and adjusting for demographic, anthropometric, and lifestyle covariates, we studied whether dietary and plasma alpha- and beta-carotene, lycopene, and alpha- and gamma-tocopherol were related to fasting and 2-h concentrations of glucose and nonesterified fatty acids during an oral-glucose-tolerance test, to the homeostasis model assessment index of insulin resistance, and to measures of beta cell function (incremental 30-min serum insulin concentration during an oral-glucose-tolerance test and first-phase insulin secretion during an intravenous-glucose-tolerance test). In men, dietary carotenoids were inversely associated with fasting plasma glucose concentrations (P < 0.05), plasma beta-carotene concentrations were inversely associated with insulin resistance (P = 0.003), and dietary lycopene was directly related to baseline serum concentrations of nonesterified fatty acids (P = 0.034). In women, dietary alpha-tocopherol and plasma beta-carotene concentrations were inversely and directly associated, respectively, with fasting plasma glucose concentrations (P < 0.05). In both sexes, cholesterol-adjusted alpha-tocopherol concentrations were directly associated with 2-h plasma glucose concentrations (P < 0.05). The data suggest an advantageous association of carotenoids, which are markers of fruit and vegetable intake, with glucose metabolism in men at high risk of type 2 diabetes.